Dampak Implementasi Pembelajaran Fiqih Terhadap Kedisiplinan Sholat Siswa MTs Ar-Rahman Nglaban Diwek Jombang - Qurrotul Ainiyah; Dewi Rahayu (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
Fiqh learning at madrasah is aimed to direct and prepare students to know, understand, appreciate and practice Islamic law in everyday life. The aim of this research was to describe student prayer discipline as an impact of the implementation of Fiqh learning at seventh grade students of MTs Ar-Rahman Nglaban Jombang. This research method was qualitative research, with qualitative descriptive design. Data collection was carried out through interviews, observation and documentation methods. Techniques for testing data validity by extending observations, increasing accuracy in research, data triangulation and using sufficient references. Data was analyzed by data collection, data reduction, data presentation and conclusion/verification. The results of the research showed that: the students were able to get used to have obligatory prayers according to what has been taught by the fiqh teacher; the increasing of students fiqih score; the students are responsible and obedient in carrying out obligatory prayers.